Cidades médias, novos espaços produtivos e reestruturação do espaço urbano em Uberaba-MG - Maria Terezinha Serafim Gomes (Confins)
In recent years, Brazilian medium-sized cities have been considered as attractive poles for both internal migration flows, and for new corporate investments in industry, trades, services and real estate, emerging new productive spaces. These cities have attracted new investments aimed at the consumer market, such as supermarkets, shopping centers, franchise stores, car dealerships, hotels and many establishments service. The attraction of new economic enterprises has led, in many cases, to a restructuring of urban space in these cities, producing new urban centralities. They come configured as emerging cities leveraging a new economic dynamics out of the metropolitan space, assuming an important role in Brazilian urban network. This article aims to discuss medium-sized cities and creation of new productive spaces as well as the restructuring of urban space, with reference to the city of Uberaba, in the Triangle region of Minas Gerais.